(untitled) (Dinamika Hukum & Masyarakat, 2023)
Abstract villages, since the enactment of Law Number 6 of 2014 concerning Villages, are getting stronger and exist as autonomous regions with the authority to regulate and manage their own affairs even down to budget and welfare matters. The law clearly states village regulations as statutory regulations stipulated by the Village Head after being discussed and agreed upon with the Village Consultative Body. This can be thought of as a small constitution where the Village looks like a small state that has its own government, they are ready with a village head who carries out the rules and has the character of an executive and also a deliberative council that looks like a village parliament that enforces these regulations and it is like a legislative body. This can lead to legal uncertainty because of the many interpretations, especially the interpretation of Article 8 of Law Number 12 Year 2011 regarding the status, position and existence of Village Regulations in the hierarchy of statutory regulations in Indonesia. Furthermore, it has an impact on village government, namely the existence of legal uncertainty, on the one hand to carry out the wheels of government, the village government must have a legal basis, namely village regulations, but on the other hand, village regulations are no longer listed in the hierarchy of State statutory regulations. Key words : Village Law, Legal Number 06 year 2014, Village political